Efficacy of essential oils of Egletes viscosa and Lippia schaueriana on the reproductive biology of Rhipicephalus sanguineus sensu lato engorged females - Pereira, Melissa Carolina [UNESP]; Anholeto, Luis Adriano; Kasa, Giovanna Gennari [UNESP]; Castro, Karina Neoob de Carvalho; Canuto, Kirley Marques; Souza, Ana Sheila de Queiroz; Camargo-Mathias, Maria Izabel [UNESP] (Elsevier, 2023)
The study analyzed the chemical composition and the acaricide effect of Egletes viscosa Less (macela-da-terra) and Lippia schaueriana Mart. (lipia-da-serra) essential oils (EOs) on Rhipicephalus sanguineus s. l. (Acari: Ixodidae) engorged females. The chemical analysis (GC-MS and GC-FID) identified 27 components in E. viscosa EO and 18 in L. schaueriana EO, which comprise more than 98% of its constituents. The effects of the oils on the reproductive biology of R. sanguineus ticks were assessed by adult immersion test. Both EOs significantly reduced (p < 0.05) the egg production index when the females were exposed to 25 and 50 mg/mL, also affecting the egg viability. During the laying process, the eggs produced by the females exposed to the EO showed several morphological alterations such as dehydrated, darkened, and disaggregated, and these alterations were more severe as the concentrations increased. The mortality percentages were 58.9%, 70.8% and 92.7% when the ticks were exposed to 12.5, 25 and 50 mg/mL of E. viscosa oil, respectively. In the same concentrations, the efficacy of L. schaueriana was 39.3%, 53.4%, and 84.6%. Therefore, it can be concluded that the essential oils of E. viscosa and L. schaueriana have acaricidal effect in females of R. sanguineus s.l ticks.
Keywords: Control; Natural acaricide; Parasite; Ticks